Walter hottle bottle - Scarffe, Bronwen (Nelson Australia South Melbourne, 1994)
Walter Hottle Bottle by Bronwen Scarffe is a delightful children's story that follows the adventures of a quirky character named Walter, who is a lovable water bottle with a personality of his own. Walter's journey takes him through various imaginative scenarios where he encounters challenges and learns valuable lessons about friendship, kindness, and the importance of staying hydrated. The narrative is infused with playful language and vibrant illustrations, making it an engaging read for young audiences. Ultimately, the story encourages children to appreciate everyday objects and highlights the significance of caring for the environment.